PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MATERI ALAT UKUR BERBASIS PROJECT BASED LEARNING (PjBL) MENGGUNAKAN CANVA DI KELAS X PROGRAM KEAHLIAN OTOMOTIF SMK GELORA JAYA NUSANTARA MEDAN - Sitompul, Riyan; Yulia, Erma; Gunawan, Safri; Tambunan, Bisrul Hapis; Sumarno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the development process, feasibility level, and effectiveness of interactive learning media based on Project-Based Learning (PjBL) using Canva, covering the topic of measuring instruments for 10th-grade students in the Automotive Engineering program at SMK Gelora Jaya Nusantara Medan. The research employs the Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects consisted of 30 10th-grade students. Data collection techniques included observation, interviews, questionnaires, and learning outcome tests (pre-test and post-test). Data analysis involved the Aiken’s V validation test and the calculation of N-Gain scores. The results indicate that the developed learning media achieved feasibility scores of 0.95 from the media expert, 0.94 from the instructional design expert, and 0.98 from the subject matter expert; all three ratings fall into the "valid" category. The large-group trial yielded an average score of 48.00 (80%), also categorized as valid. Effectiveness testing using N-Gain scores demonstrated that the learning media is effective in improving student learning outcomes. Thus, the Canva-based, PjBL-oriented interactive learning media for measuring instruments is proven to be feasible and effective for implementation in automotive vocational education.